Advancing cross-national planning and partnership: Proceedings from the International Multimorbidity Symposium 2019. (21st September 2020) - Nicholson, Kathryn; De Burghgraeve, Tine; Fortin, Martin; Griffith, Lauren E; Licher, Silvan; Lizotte, Daniel; Mair, Frances S; Miozzo, Ruben; Nouri, Maede Sadat; Ryan, Bridget L; Lee, Eng Sing; Smith, Susan; et al.
The International Multimorbidity Symposium was held in November 2019 at Western University to achieve three main objectives: to discuss progress and findings from various jurisdictions; to facilitate collaboration through group discussion to identify strategies to move multimorbidity research forward; and to create concrete plans to ensure advances in multimorbidity research and knowledge can be achieved through cross-national partnership. This event included keynote presentations, elevator pitch presentations and breakout sessions and there was a total of 35 attendees from eight countries, representing diverse disciplines and training levels. The overall themes arising from the event were: the importance of integrating the study and management of multimorbidity from both the primary care and public health perspectives; meaningful engagement and collaboration with patients and caregivers to understand key dimensions of multimorbidity; the considerable benefit of collaborative international partnerships; and the need to spread and scale innovations for health care systems that can better respond to the complex needs of patients and caregivers who are living with multimorbidity. Finally, it was well-acknowledged among the attendees that expanding the collaboration and discussion among international colleagues via in-person and virtual events will be important to move multimorbidity research forward.